Prinsip Dasar Manajemen Keuangan Dan Risiko Untuk Lembaga Keuangan Era Digital - ANANTA UPA, VIERLY; MUDJI (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
This research is to analyze how the development of the world financial system has led to the increasing importance of the role of professional management of financial institutions. Financial institutions are institutions that manage financial resources from other parties to be used for more productive activities. Advances in technology, information systems, and market openness at an increasingly wide level, for example, at the global level, require financial institutions to be more careful in managing their businesses so as not to fall into losses that could involve many parties. This potential loss can arise from the failure of the institution to manage the risks faced, both financial risks, business risks, and system risks. Therefore, good risk management for a financial institution is a must.